Evaluating Firm Value in Indonesian State-Owned Enterprises: The Roles of Efficiency, Profitability, and Board Independence - Pramono, Aria Bimo Setyo; Bustaman, Yosman (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the impact of profitability, operational efficiency, and corporate governance on firm value in Indonesian State-Owned Enterprises listed on the Indonesia Stock Exchange from 2017 to 2023. Using a quantitative approach with panel data regression (fixed effect model), the analysis encompasses 119 observations from 17 State-Owned Enterprises. Profitability is measured by Return on Assets, operational efficiency by Data Envelopment Analysis, and firm value by Tobin’s Q and Market-to-Book Value. Corporate governance is assessed through the proportion and tenure of politically affiliated independent commissioners. Results reveal that profitability (p=0.0042 for Tobin’s Q; p=0.0326 for Market-to-Book Value) and efficiency (p=0.0119 for Tobin’s Q; p=0.0495 for Market-to-Book Value) significantly enhance firm valuation. Tenure of independent commissioners significantly affects Tobin’s Q (p=0.0204) but not Market-to-Book Value, while their proportion shows no significant impact. These findings highlight the critical role of financial and operational performance in driving State-Owned Enterprises valuation, with governance effects moderated by political affiliations. Policymakers should prioritize operational efficiency and board expertise in State-Owned Enterprises reforms to enhance market performance. Future research could explore qualitative governance dynamics to further understand valuation in State-Owned Enterprises.